การออพติไมซ์การเผาไหม้ร่วมในฟลูอิดไดซ์เบดแบบหมุนเวียนของขยะพลาสติกและชีวมวล - ศิริวรรณ ศุภาดารัตนาวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
In this work, combustion of plastic waste and biomass in circulating fluidized bed combustor is investigated by using commercial software and improved combustion model. The research procedure includes characterization of fuel, selection of thermodynamic model and defining geometry of the chemical unit operation. The results showed that the conditions producing highest carbon combustion efficiency with greater than 98%, low CO, low SO[subscript 2] and NO[subscript x] released are the combustion temperature at 900 degress celsius, the excess feed air 120%, the ratio of Ca/S at 1 and moisture content in fuel lower than 10%. In addition, the relevant flow test unit for the combustor is devised to study the behavior of the swirl and the effect of the vortex ring. It was found that the swirled flow and the vortex ring play important roles to prevent the escape of unburned particle. Consequently, the swirled flow and the vortex ring can improve combustion efficiency.